Espiritualidad: un abordaje interdisciplinario - Lemos, Rosalba (2023)
Both the theology of Christian spirituality and transpersonal psychology confirm that there is no known division of body and spirit, embodiment evidence among other characteristics: identity, individuality and space-time location in humans, being fully aware of it, facilitates a step toward understanding the self, being in the world and the transcendence. Spirituality is the path from fundamental questions of life to the search, recognition, and continuous intimate contact about that actually it is, which allows establishing strong and true relationships with yourself, with the others, with that and with God himself.